"Agrarian Crisis in Kashmir During the Sikh Rule (1819-1846)" - Tanveer Ul Islam Khan; Showkat Ahmad Mir; Gawher Ahmad Bhat (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The conquest of Kashmir by Maharaja Ranjit Singh in 1819 had a profound impact on the economy of Kashmir especially on agriculture which was the backbone of the economy. During the twentyseven years of Sikh rule, Kashmir was governed through a chain of ten governors. To fill the coffers of the Lahore treasury and to fill their own pockets, these governors not only continued the oppressive taxation of their predecessors but also devised new mechanisms of exploitation and oppression. As a corollary, Kashmiri people in general and peasantry, in particular, witnessed unparallel economic repression which caused an agrarian crisis. The present paper is, therefore, aimed to unravel those causes which led to this crisis. Moreover, how the State suffered in terms of revenue due to this crisis has also been explored in the paper.